Analysing Torque-slip Characteristic of a Small Power Induction Motor Operating under Geophysical Conditions - Smolskas, Pranas; Zmuida, Mykolas (Elektronika ir Elektrotechnika, 2016)
The article analyses the torque-slip characteristic of a small power induction motor up to 50 W used in mechatronic system drives of a borehole investigation devices, that works at a wide range of temperature (from -20 oC to +150 oC) and is supplied through a long geophysical cable with complex impedance. The external diameter of the induction motor is up to 36 mm, the number of stator teeth is 8. The torque-slip characteristics have been calculated for different cases, when the stator winding is single-layer, two-layer short-pitch and sinusoidal, motor rotor is solid and copper-cage solid. The calculated torque-slip characteristics at environment temperature +20 oC were compared with the tested performed experiments. DOI: http://dx.doi.org/10.5755/j01.eee.22.1.7065